2003
DOI: 10.1021/ja034440c
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Phosphotyrosine Mimetic for PTP1B Using Breakaway Tethering

Abstract: Protein tyrosine phosphatases play important roles in many signaling cascades involved in human disease. The identification of druglike inhibitors for these targets is a major challenge, and the discovery of suitable phosphotyrosine (pY) mimetics remains one of the key difficulties. Here we describe an extension of tethering technology, "breakaway tethering", which is ideally suited for discovering such new chemical entities. The approach involves first irreversibly modifying a protein with an extender that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…Because the binding of the fragment is stabilized by the reversible disulfide bond, tethering is especially powerful for identifying very weak interactions and enables the exploration of binding sites not easily accessible to NMR, SPR, or functional screening approaches. Sunesis used the disulfide-trapping (Erlanson et al 2003a;Yang et al 2009;Cancilla et al 2008) and also reported examples in which tethering identified previously unknown sites that allosterically regulated protein activity (Erlanson et al 2003b;Hardy and Wells 2009).…”
Section: Ligand-binding Potential and Surface Plasticity Of Il-2mentioning
confidence: 99%
“…Because the binding of the fragment is stabilized by the reversible disulfide bond, tethering is especially powerful for identifying very weak interactions and enables the exploration of binding sites not easily accessible to NMR, SPR, or functional screening approaches. Sunesis used the disulfide-trapping (Erlanson et al 2003a;Yang et al 2009;Cancilla et al 2008) and also reported examples in which tethering identified previously unknown sites that allosterically regulated protein activity (Erlanson et al 2003b;Hardy and Wells 2009).…”
Section: Ligand-binding Potential and Surface Plasticity Of Il-2mentioning
confidence: 99%
“…Productive binding fragments are captured under equilibrium conditions by reversible thioldisulfide interchange (10). Fragments from Tethering have been used to nucleate and augment the identification of potent compounds that target both enzymes and protein-protein interfaces (10)(11)(12)(13)(14). We present this work on the caspases as an approach for the simultaneous discovery of an allosteric site and compounds that affect this site.…”
mentioning
confidence: 99%
“…Erlanson et al applied disulfide tethering to identify a weak active site fragment binder of PTP1B. [61] The catalytic cysteine, at the bottom of the narrow active site channel in PTP1B, was considered inappropriate for disulfide tethering. The residues surrounding the active site pocket were considered crucial to maintain the finely tuned, delicate catalytic machinery.…”
Section: Tethering With Breakaway Extenders -Protein Tyrosine Phosphamentioning
confidence: 99%
“…[61] A cysteine was introduced far from the active site and subsequently modified with breakaway extender 16, composed of a reactive bromoacetamide and a pTyr mimic, Figure 8. The pTyr mimic binds to the active site pocket protecting the active site cysteine from alkylation and positioning the bromoacetamide close to the mutant cysteine for covalent modification, Figure 9.…”
Section: Tethering With Breakaway Extenders -Protein Tyrosine Phosphamentioning
confidence: 99%